Study of Ahkam's Hadith on the Protection of Women in Cases of Domestic Violence - Abdillah Wahid, Ahsan; Taufiq Hidayatur Rohman, Ahmad (Rechtsvinding, 2025)
This study aims to analyze Ahkam's Hadith related to the protection of women in cases of Domestic Violence (KDRT) with a focus on the definition of domestic violence in the perspective of Islamic law, the Concept of Women's Protection in Islam, the Analysis of Ahkam's Hadith on the Protection of Women from Domestic Violence, and the Relevance of Ahkam Hadith in the Modern Context. The research method used is a literature study with a qualitative-descriptive approach, where primary and secondary sources, including hadith books, classical Islamic literature, and domestic violence laws in Indonesia, are then critically analyzed. The results of the study show that Hadith Ahkam expressly prohibits all forms of violence against women and supports women's rights to be protected in the household, which is in line with the principles of positive law in Indonesia. Ahkam's hadith has strong relevance in the modern context and can serve as a moral and legal foundation in protecting women from domestic violence. The implication of this study is the need to strengthen education and legal awareness among Muslims regarding women's rights, as well as the integration of Islamic principles in broader public policy. Recommendations for further research are to examine the role of Islamic institutions in the prevention of domestic violence and conduct comparative studies on the application of Islamic law in various Muslim-majority countries to identify best practices that can be adopted in the Indonesian context.